2022
DOI: 10.3892/br.2022.1586
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long‑term psychiatric symptoms associated with COVID‑19 (Review)

Abstract: Coronavirus disease 2019 (COVID-19) started spreading at the end of 2019 and despite the immediate actions of various governments with strict control, more and more individuals became infected daily. Due to the uncertainty and insecurity that still exists around this pandemic, there is an acute need for information and knowledge of what severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection entails. Respiratory and other physical symptoms received most of the medical attention, however, infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Persistent symptoms may include fatigue, post-exertional malaise, and multiple emotional and cognitive impairments (memory impairment, attention deficits, cognitive difficulties, executive dysfunction) [ 422 ]. In addition to cognitive deficits, mental symptoms include anxiety, depression, mood swings, bipolar/manic episodes, obsessive–compulsive disorders, posttraumatic stress, new-onset psychosis, sleep disturbances, substance use disorders, suicidality, and symptom constellations consistent with pediatric acute-onset neuropsychiatric syndrome (PANS; see Section 3.8.5 for additional PANS information) [ 5 , 50 , 81 , 82 , 83 , 84 , 85 , 422 , 425 , 426 , 427 , 428 , 429 , 430 , 431 , 432 ]. One retrospective cohort study using electronic health record data comprising 81 million patients in healthcare organizations primarily in the US showed that the risk of common neuropsychiatric disorders (mood disorders, anxiety disorders) returned to baseline in 1–2 months, but there remained an elevated risk of psychotic disorders, cognitive deficit, dementia, and seizures at two years of follow-up [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Persistent symptoms may include fatigue, post-exertional malaise, and multiple emotional and cognitive impairments (memory impairment, attention deficits, cognitive difficulties, executive dysfunction) [ 422 ]. In addition to cognitive deficits, mental symptoms include anxiety, depression, mood swings, bipolar/manic episodes, obsessive–compulsive disorders, posttraumatic stress, new-onset psychosis, sleep disturbances, substance use disorders, suicidality, and symptom constellations consistent with pediatric acute-onset neuropsychiatric syndrome (PANS; see Section 3.8.5 for additional PANS information) [ 5 , 50 , 81 , 82 , 83 , 84 , 85 , 422 , 425 , 426 , 427 , 428 , 429 , 430 , 431 , 432 ]. One retrospective cohort study using electronic health record data comprising 81 million patients in healthcare organizations primarily in the US showed that the risk of common neuropsychiatric disorders (mood disorders, anxiety disorders) returned to baseline in 1–2 months, but there remained an elevated risk of psychotic disorders, cognitive deficit, dementia, and seizures at two years of follow-up [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Known predisposing factors for a diagnosis of long COVID-19 include female sex, belonging to an ethnic minority, socioeconomic deprivation, severe initial illness, smoking, obesity, and a wide range of comorbidities (3,9). Although psychological distress has been linked to longer symptoms of viral infections (10,11) and a bidirectional relationship between SARS-CoV-2 infection and psychiatric diagnoses has been described (12)(13)(14)(15)(16), the relationship between preexisting psychiatric conditions and the risk for long COVID is still being elucidated. Recent evidence suggests that preinfection depression and anxiety are associated with an increased risk of a diagnosis of long COVID after initial infection (11,17).…”
Section: Introductionmentioning
confidence: 99%
“…The psychological implications of the COVID-19 pandemic may exceed those of previous outbreaks, as COVID-19 has been found to increase the susceptibility of developing mental, cognitive, and sleep disturbances, not only during its acute phase but even after discharge [2]. Psychological distress and sleep dysfunction appear to be caused by a variety of stressors and psychosocial factors, such as isolation and socioeconomic difficulties, the often-required hospitalization, and also by the direct bio-immunologic effects of the virus itself [3] .…”
Section: Introductionmentioning
confidence: 99%